2018
DOI: 10.1371/journal.pbio.2005093
|View full text |Cite
|
Sign up to set email alerts
|

A revised understanding of Tribolium morphogenesis further reconciles short and long germ development

Abstract: In Drosophila melanogaster, the germband forms directly on the egg surface and solely consists of embryonic tissue. In contrast, most insect embryos undergo a complicated set of tissue rearrangements to generate a condensed, multilayered germband. The ventral side of the germband is embryonic, while the dorsal side is thought to be an extraembryonic tissue called the amnion. While this tissue organisation has been accepted for decades and has been widely reported in insects, its accuracy has not been directly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…In the beetle Tribolium, split-embryo experiments have confirmed that this variability results from a temporally dynamic 'segmentation clock' within individuals rather than spatially variable expression between individuals (Sarrazin et al, 2012). Expression dynamicity has also been demonstrated in Tribolium by comparing the average patterns of finely staged cohorts of embryos, by visualising discrepancies between the transcript and protein domains of a given gene, and by gaining an understanding of cell dynamics within the SAZ via live imaging (Benton, 2018;El-Sherif et al, 2012;Sarrazin et al, 2012). In other species, gene expression dynamics within the SAZ have rarely been studied in detail.…”
Section: Nature Of the Arthropod Segmentation Clockmentioning
confidence: 95%
See 1 more Smart Citation
“…In the beetle Tribolium, split-embryo experiments have confirmed that this variability results from a temporally dynamic 'segmentation clock' within individuals rather than spatially variable expression between individuals (Sarrazin et al, 2012). Expression dynamicity has also been demonstrated in Tribolium by comparing the average patterns of finely staged cohorts of embryos, by visualising discrepancies between the transcript and protein domains of a given gene, and by gaining an understanding of cell dynamics within the SAZ via live imaging (Benton, 2018;El-Sherif et al, 2012;Sarrazin et al, 2012). In other species, gene expression dynamics within the SAZ have rarely been studied in detail.…”
Section: Nature Of the Arthropod Segmentation Clockmentioning
confidence: 95%
“…'SAZ' is now preferred over the traditional term 'growth zone', because it makes no assumption of localised and continuous cell proliferation in the posterior of the embryo (Janssen et al, 2010). The material for new segments is generally provided by a combination of cell division and convergent extension, butas in vertebratesthe relative contributions of these cell behaviours to axial elongation vary widely across species (Auman et al, 2017;Benton, 2018;Benton et al, 2016;Mito et al, 2011;Nakamoto et al, 2015;Steventon et al, 2016). Accordingly, although cell division may in some species be coordinated with segment addition, segment patterning processes do not appear to be mechanistically dependent on the cell cycle (Cepeda et al, 2017), aside from in special cases such as malacostracan crustaceans.…”
Section: Sequential Segmentation and The Segment Addition Zonementioning
confidence: 99%
“…Since ectopic segment formation after mlpt RNAi occurs in a low frequency in R. prolixus, it is possible that it also occurs at low frequency in O. fasciatus and G. buenoi mlpt knockdown. It is intriguing that, in these three species, mlpt is mainly required when germ band elongation and abdominal segmentation takes place and future studies using embryonic live imaging, as recently described for other insect species (Benton, 2018), might help to understand the role of mlpt during germ band elongation and thoracic vs. abdominal segment specification.…”
Section: Conservation Of Mlpt Expression Among Insectsmentioning
confidence: 94%
“…Segments are added at an average rate slightly less than one segment per hour at 30 °C (0.7 segments/h or 1.4 h per segment). The regularity of segment addition is unaffected by either the first molt (~ 4 h post-hatching, see Additional file 2 for how first molt was determined) or the transitions between addition of thoracic (post-maxillary segments, 1-11), genital (12,13), and abdominal segments (14-19, Additional file 1). Within 18 h at 30 °C, larvae add 14 segments, and the overall length of the body roughly doubles ( Fig.…”
Section: Segment Addition and Morphogenesis Occur Progressively In Thmentioning
confidence: 99%
“…Because most species elongate significantly during segmentation, classical concepts of posterior growth generally invoke mitosis, either in posterior stem cells or in a vaguely defined posterior region of proliferation [4][5][6][7][8]. Cell movement has also been assumed to play a role in elongation in cases where embryonic shape changes dramatically [7][8][9][10]-and is documented in the flour beetle, Tribolium castaneum [11][12][13]. The current descriptive data suggest a large degree of variability in how sequentially segmenting arthropod embryos grow (reviewed in [7,14,15]).…”
Section: Introductionmentioning
confidence: 99%